(untitled) (Jagannath University Journal of Life and Earth Sciences, 2024)
Bangladesh is one of the nations that has a distinctive environment for floods. Most of the land is low-lying, and 80% is a floodplain, making it highly susceptible to frequent flooding. This research aims to investigate the susceptibility of riverine communities to flooding and display the spatial distribution of vulnerability for the study region (Harirampur Upazila). A vulnerability assessment index is developed using multiple variables related to social, physical, and economic vulnerability. A quantitative survey is conducted to gather data on physical, social, and economic factors contributing to household vulnerability to floods. The results reveal that out of the five unions in Harirampur Upazila, Gopinathpur, and Lesraganj unions, they have been found to have a high vulnerability to flooding (vulnerability scores of 3.19 and 3.10, respectively). Kanchanpur Union is severely vulnerable to flooding (score 3.57). On the other hand, Gala Union is designated as a lowly vulnerable (score of 2.23) area, and Ramkrishnapur Union is classified as a moderately vulnerable (score of 2.83) area. Finally, this study would help to assign government and non-government initiatives following the vulnerability category during critical conditions of any disaster period. Jagannath University Journal of Life and Earth Sciences, 9(2): 195-214, 2023 (December)